Comparative study of a concentrated photovoltaic-thermoelectric system with and without flat plate heat pipe. (1st August 2019) - Shittu, Samson; Li, Guiqiang; Zhao, Xudong; Akhlaghi, Yousef Golizadeh; Ma, Xiaoli; Yu, Min
Highlights: Hybrid photovoltaic-thermoelectric systems with and without heat pipe are studied. Comparison of the photovoltaic only and hybrid photovoltaic systems is presented. Influence of concentration ratio, ambient temperature, wind speed is investigated. Three-dimensional numerical simulation using finite element method is presented. Abstract: Thermal management of photovoltaic cells is an essential research objective for increasing the conversion efficiency of the photovoltaic. Flat plate heat pipe is a passive cooling device capable of effectively reducing the solar cell temperature. Therefore, this study presents a numerical investigation of a hybrid photovoltaic-thermoelectric system with and without a flat plate heat pipe. A detailed comparative analysis of the electrical performance of the photovoltaic only, photovoltaic-thermoelectric and photovoltaic-thermoelectric-heat pipe systems is performed. The influence of solar concentration ratio, ambient temperature, wind speed and thermoelectric generator cold side temperature on the efficiency and power output of the photovoltaic only and hybrid photovoltaic-thermoelectric systems are studied using COMSOL 5.4 Multiphysics software. A three-dimensional finite element study is carried out and temperature dependent thermoelectric material properties are considered to increase the simulation accuracy. Results show that the photovoltaic-thermoelectric-heat pipe efficiency is 1.47% and 61.01% higher compared to that of the photovoltaic-thermoelectric and photovoltaic only systems respectively at a concentration ratio of 6. In addition, the photovoltaic-thermoelectric-heat pipe is recommended for highly concentrated systems because of its superior performance. Furthermore, the photovoltaic-thermoelectric system is a better alternative to the photovoltaic only system because of its enhanced performance which is second only to that of the photovoltaic-thermoelectric-heat pipe system. Results also show that ineffective cooling of the thermoelectric generator can adversely affect the performance of the hybrid systems. This study will proper valuable information on the feasibility of hybrid photovoltaic-thermoelectric systems with and without heat pipe. Finally, the three-dimensional nature of this study makes it very useful in understanding the actual temperature distribution in the hybrid systems.